Fault Diagnostic of Rotating Machines Based on Artificial Intelligence: Case Studies of the Centrais Elétricas do Norte do Brazil S/A – Eletrobras-Eletronorte - Moutinho, Marcelo Nascimento (IntechOpen, 2012)
None